Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 116059 by Study last updated on 30/Sep/20

Σ_(n=1) ^∞ ((n!)/3^(n+1) )

n=1n!3n+1

Answered by MWSuSon last updated on 30/Sep/20

Do you want to test for convergence?

Doyouwanttotestforconvergence?

Answered by mathmax by abdo last updated on 30/Sep/20

let s(x) =Σ_(n=1) ^∞  n! x^(n+1)  ⇒s^′ (x) =Σ_(n=1) ^∞ (n+1)! x^n  =Σ_(n=2) ^∞ n! x^(n−1)   =(1/x^2 )Σ_(n=2) ^∞ n! x^(n+1)  =(1/x^2 ){Σ_(n=1) ^∞  n! x^(n+1) −x^2 }=(1/x^2 )s(x)−1 ⇒  s^′ (x) =((s(x))/x^2 )−1 ⇒x^2 s^′ (x) =s(x)−x^2  ⇒x^2 s^′ (x)−s(x)+x^2  =0   (∣x∣<1)  let solve x^2 y^′ −y =−x^2   h→x^2 y^′  =y ⇒(y^′ /y) =(1/x^2 ) ⇒ln∣y∣ =−(1/x) +c ⇒y =k e^(−(1/x))   lagrange method →y^′  =k^′  e^(−(1/x))   +k((1/x^2 ))e^(−(1/x))   e⇒x^2 k^′  e^(−(1/x))  +k e^(−(1/x)) −ke^(−(1/x))  =−x^2  ⇒k^′  e^(−(1/x))  =−1 ⇒  k^′  =−e^(1/x)  ⇒k(x) =−∫_x ^1 e^(1/x) dx+c ⇒  s(x) =e^(−(1/x)) { c−∫_x ^1  e^(1/x) dx } ⇒s((1/3)) =e^(−(1/3)) {c−∫_(1/3) ^1  e^(1/x) dx}  ....be continued...

lets(x)=n=1n!xn+1s(x)=n=1(n+1)!xn=n=2n!xn1=1x2n=2n!xn+1=1x2{n=1n!xn+1x2}=1x2s(x)1s(x)=s(x)x21x2s(x)=s(x)x2x2s(x)s(x)+x2=0(x∣<1)letsolvex2yy=x2hx2y=yyy=1x2lny=1x+cy=ke1xlagrangemethody=ke1x+k(1x2)e1xex2ke1x+ke1xke1x=x2ke1x=1k=e1xk(x)=x1e1xdx+cs(x)=e1x{cx1e1xdx}s(13)=e13{c131e1xdx}....becontinued...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com